Implementasi Strategi Komunikasi Internal melalui Podcast dan Video Digital di Yayasan Karya Bakti United Tractors - Dinda Nailul Fauziah; Hari Otang Sasmita (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The digital era encourages organizations to adopt flexible communication media for knowledge management. This study aims to analyze the implementation of internal communication strategies through podcasts and digital videos within the knowledge management program at Yayasan Karya Bakti United Tractors (YKBUT). Using a practice-based qualitative descriptive approach, data collection involved participatory observation, focused discussions, and documentation study of viewership metrics. The results indicate that audiovisual digitization effectively documents tacit knowledge into an accessible format. Despite facing operational challenges regarding the temporary absence of technical staff, the division successfully adapted through standardized work instruction matrix, producing three live podcasts and four repurposed digital videos called KAJOL. Metric evaluation demonstrated broad internal audience reach, with psychological well-being topics dominating 36% of total views. This implies that internal communication effectiveness relies heavily on concise content repurposing innovations and personal relevance. Therefore, organizations are highly recommended to maintain content repurposing strategies and increase non-technical competency materials.